2001
DOI: 10.1128/jcm.39.7.2379-2385.2001
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of the VITEK 2 System and the Advanced Expert System on the Clinical Laboratory of a University-Based Hospital

Abstract: A study was designed to assess the impact of the VITEK 2 automated system and the Advanced Expert System (AES) on the clinical laboratory of a typical university-based hospital. A total of 259 consecutive, nonduplicate isolates of Enterobacteriaceae members, Pseudomonas aeruginosa, and Staphylococcus aureus were collected and tested by the VITEK 2 system for identification and antimicrobial susceptibility testing, and the results were analyzed by the AES. The results were also analyzed by a human expert and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 7 publications
(4 reference statements)
2
32
1
Order By: Relevance
“…Canton et al (25) found the VITEK 2 method less reliable than the microdiffusion method, whereas Leclercq et al (26) stated that VITEK 2 was more reliable than the agar dilution method. According to Nyberg et al (27), sensitivity and specificity vary in different studies, but high sensitivity and specificity have been achieved with VITEK 2 when testing K. pneumoniae isolates (15,27,28). They also claimed that VITEK 2 AES was excellent compared to genotypic ESBL determination and it was very comparable to the agar dilution and diffusion methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canton et al (25) found the VITEK 2 method less reliable than the microdiffusion method, whereas Leclercq et al (26) stated that VITEK 2 was more reliable than the agar dilution method. According to Nyberg et al (27), sensitivity and specificity vary in different studies, but high sensitivity and specificity have been achieved with VITEK 2 when testing K. pneumoniae isolates (15,27,28). They also claimed that VITEK 2 AES was excellent compared to genotypic ESBL determination and it was very comparable to the agar dilution and diffusion methods.…”
Section: Discussionmentioning
confidence: 99%
“…The VITEK 2 advanced expert system (AES) is an automated system that uses antimicrobial susceptibility data to suggest the phenotype of the tested isolate and thereby determine its susceptibility or resistance to antibiotics (15).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, an automated system that utilizes an ESBL confirmatory test and an expert system should accurately discriminate ESBLs from other ␤-lactamases and provide interpretations and recommendations that do not require additional input by laboratory personnel (10). Inconclusive or incorrect comments are likely to frustrate and cause confusion and may delay or even prevent the issue of a clinically useful report to the clinician.…”
Section: Discussionmentioning
confidence: 99%
“…The AES may also suggest a change in an interpretation from sensitive (S) to intermediate (I) or resistant (R), based on recognized resistance mechanisms, to prevent therapeutic failure. These changes of interpretation are according to the software parameters defined by the user (19). For the tests in the present study, interpretations as recommended by the National Committee for Clinical Laboratory Standards (15) and the AES configuration parameters set "natural resistance," "European hospitals," "never more susceptible," and "least risk" were used.…”
Section: Methodsmentioning
confidence: 99%